2014
DOI: 10.12691/ajmbr-2-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefits of Al-hijamah: in Light of Modern Medicine and Prophetic Medicine

Abstract: Excretory treatment modalities that excrete pathological substances outside human body deserve more research attention as this may potentiate the therapeutic effects of pharmacological treatments. Overcoming language barrier through translating the national medical literature to medical English to be introduced to the international medical literature is vital. Wet cupping therapy (WCT) of prophetic medicine (Al-hijamah) is practiced in the Arabic medical literature where it is reported to treat many diseases d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 100 publications
(134 reference statements)
0
18
0
1
Order By: Relevance
“…Many studies confirmed the effect of oil massage on the GI system, especially regarding the effect of Chamomile on improving the bowel movement (35). Moreover, cupping on belly and areas around the uterus was performed to achieve in this regard since cupping causes more absorption of blood flow in the area and warms the organ and drains the aggregated harmful excretions from the uterus to the skin in order to remove them (36,37). Additionally, improving the function of the GI system resulted in resolving the uterus problems to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies confirmed the effect of oil massage on the GI system, especially regarding the effect of Chamomile on improving the bowel movement (35). Moreover, cupping on belly and areas around the uterus was performed to achieve in this regard since cupping causes more absorption of blood flow in the area and warms the organ and drains the aggregated harmful excretions from the uterus to the skin in order to remove them (36,37). Additionally, improving the function of the GI system resulted in resolving the uterus problems to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune diseases, it was suggested that hijama improved symptoms of the disease by clearing blood and interstitial fluid from the noxious substances such as auto-antibodies, immune complexes, pro-inflammatory mediators, cytokines, oxidants, and soluble cytokine receptors. [13][14][15][16] This immune-modulatory effect was described in rheumatoid arthritis, where hijama induced significant reduction in rheumatoid factor and soluble interleukin-2 receptors along with clinical improvement including pain and arthritis. 17 Several authors have studied the efficacy of hijama in various inflammatory, autoimmune or infectious conditions such as asthma, psoriasis, facial paralysis, herpes zoster, cervical spondylitis, and acne.…”
mentioning
confidence: 85%
“…30 Other data from literature suggested that hijama helps restoring humoral immunity and tissue homeostasis by clearing up serum and interstitial fluid from noxious substances that sustain inflammation. [13][14][15][16] Some studies suggested that toxic metals can increase the risk of developing thyroid diseases. 31,32 Moreover, mercury can play a role in the pathogenesis of autoimmune thyroiditis by triggering autoimmune reactions and oxidative damage.…”
mentioning
confidence: 99%
“…Durasi terapi bekam secara keseluruhan dari tahapan bekam kering hingga pembersihan darah dari bekam basah di antara 25-30 menit. Adapun durasi bekam basah sekitar 5-10 menit, dan tidak disarankan lebih dari 10 menit (S. M. El Sayed et al, 2014). Beberapa efek samping dari bekam basah pada jaringan kulit adalah munculnya eritema, bengkak dan bula jika dilakukan tidak dengan hati-hati (Al-rubaye, 2012).…”
Section: Diagram Bloxplot Jumlah Lokasi Titik Bekam Dengan Nilai Seliunclassified